1993
DOI: 10.1039/p19930002781
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reaction of 3-hydroxy-1-(o-methylaryl)alkan-1-ones: formation of cyclopropane-1,2-diols and benzocyclobutenols through β- and γ-hydrogen abstractions

Abstract: Irradiation of 3-hydroxy-2,2-dimethyl-l-(0-methylary1)-alkan-1 -ones 1 a-h having a bulky alkyl group or an aryl group on C-3 in methanol gave trans-and cis-cyclopropane-1.2-diols 2a-g and 3a. c-f, h and benzocyclobutenols 4a-h through pand y-hydrogen abstractions. Irradiation of 3hydroxy-2.2dimethyl-I -(o-methylpheny1)-alkan-1 -ones 1 i-k having ethyl, methyl or no substituent at C-3 gave benzocyclobutenols 4i-k and 1,3-diketones 5i, j, but no cyclopropane-l,2-diols. The cyclopropane-1,2-diols were sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Thus, the ratio of the naphthalenone 9 to the benzocyclobutenol 10 became lower with the bulkier ortho alkyl group, reflecting the steric hindrance leading to 9 . Contrary to the photoreactions of 4a , e , f in methanol, irradiation of them in hexane gave benzocyclobutenols 10a , e , f exclusively, as was observed in our previous reports. ,
3
4
…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, the ratio of the naphthalenone 9 to the benzocyclobutenol 10 became lower with the bulkier ortho alkyl group, reflecting the steric hindrance leading to 9 . Contrary to the photoreactions of 4a , e , f in methanol, irradiation of them in hexane gave benzocyclobutenols 10a , e , f exclusively, as was observed in our previous reports. ,
3
4
…”
Section: Resultssupporting
confidence: 77%
“…We have already reported that 1-( o -methylphenyl)-2,2-dimethyl 1,3-diketones underwent photocyclization in hexane to afford benzocyclobutenols efficiently because the reverse transfer of hydrogen in the intermediary 1,4-diradicals to reproduce the starting ketones was suppressed owing to intramolecular hydrogen bonding. , We also reported on the photochemical reactions of β-hydroxy ketones in which β-hydrogen abstraction occurred competitively with γ-hydrogen abstraction . Because of our interest in the effect of β-functional groups on the photoreactivity of o -alkylaryl ketones, we now report novel selective photochemical reactions of 3-(2-alkylphenyl)-2,2-dimethyl-3-oxopropanoates and their related compounds having an amide group in the β-position.…”
Section: Introductionmentioning
confidence: 99%
“…The compound 2a had higher R f value than 3a , so a similar relation would be expected for 2b − e and 3b − e . The photocyclization of hydroxy ketones 1f − h which had an ortho methyl group to give 2f − h and 3f − h took place more rapidly than that of 1a − e under the same conditions. The C(2‘)-methyl groups in 2a − e and 3a − e interact severely with the hydroxyalkyl group on C(1‘).…”
Section: Resultsmentioning
confidence: 97%
“…Irradiation of the hydroxy ketone 1a in methanol with Pyrexfiltered light gave two diastereomeric 1,2-dihydrobenzocyclobutenols 2a and 3a together with trans-and cis-cyclopropane-1,2-diols 4 (Scheme 1). 6 The 1,2-dihydrobenzocyclobutenols 2a and 3a could be isolated by column chromatography on silica. The configuration of 2a was determined by X-ray crystallographic analysis to be (3S*,1ЈS*), so that 3a had the (3S*,1ЈR*) configuration.…”
Section: Resultsmentioning
confidence: 99%